2008
DOI: 10.1016/j.comppsych.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Time to emergence of severe suicidal ideation among psychiatric patients as a function of suicide attempt history

Abstract: Background-Little is known about the emergence of suicidal ideation among psychiatric inpatients with histories of no, single, or multiple suicide attempts. We investigated differences in time to reemergence of severe suicidal ideation among psychiatric patients as a function of their suicide attempt histories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The presence of a recent suicide attempt is necessary to meet the risk criteria for the high‐level acute risk group. There is a significant amount of empirical evidence demonstrating that prior suicide attempts are significant risk factors for future suicide attempts (Andover et al., 2008; Kuehn et al., 2020; Irigoyen et al., 2019); however, there is a gap in the literature regarding how to evaluate the importance of the recency of the attempt as it relates to suicide current risk. That is, at what point is a suicide attempt no longer “recent?” For example, it would not be uncommon for a provider to consider risk level differently when evaluating an individual who attempted suicide 20 years ago and displays no current suicidal ideation or relevant acute risk factors for suicide versus a patient who has attempted suicide within the past year but displays none of the current acute suicide risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a recent suicide attempt is necessary to meet the risk criteria for the high‐level acute risk group. There is a significant amount of empirical evidence demonstrating that prior suicide attempts are significant risk factors for future suicide attempts (Andover et al., 2008; Kuehn et al., 2020; Irigoyen et al., 2019); however, there is a gap in the literature regarding how to evaluate the importance of the recency of the attempt as it relates to suicide current risk. That is, at what point is a suicide attempt no longer “recent?” For example, it would not be uncommon for a provider to consider risk level differently when evaluating an individual who attempted suicide 20 years ago and displays no current suicidal ideation or relevant acute risk factors for suicide versus a patient who has attempted suicide within the past year but displays none of the current acute suicide risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Often, there are protocols or guidelines that clinicians and researchers are required to follow when determining suicide risk levels based on these risk factors. For example, there is a significant amount of empirical evidence demonstrating that prior suicidal thoughts and behaviors are significant risk factors for future suicide attempts (Andover et al., 2008; Kuehn et al., 2020; Irigoyen et al., 2019). As a result, suicidal thoughts and attempts are often treated as homogeneous constructs that confer a high risk for suicide.…”
mentioning
confidence: 99%
“…This may commence a vicious cycle, since Andover, Gibb, and Miller (2008) found that a history of suicide attempts favors the occurrence of severe suicidal ideation. Nevertheless, suicidal ideation shows a low correlation with the lethality of suicide attempts (Large & Nielssen, 2012), at least independently of other risk factors such as mental disorders, gender and previous suicide attempts (Borges et al, 2010;Diaz et al, 2003;Scocco et al, 2008).…”
Section: Suicide Continuummentioning
confidence: 98%
“…Patients with repeated episodes were more likely to experience higher levels of suicidal ideation at discharge interview. Andover et al [4] reported that multiple and single attempters did not differ in time to the emergence of severe suicidal ideation. Further, they hypothesized that multiple attempters may be more likely to act on this ideation and make a subsequent attempt.…”
Section: Discussionmentioning
confidence: 99%
“…The existing researches consistently report that a history of previous suiciderelated behavior (SRB) is a statistically significant risk factor for future suicidal behaviors [1][2][3][4][5][6][7] and eventual suicide [1,2]. The identification of patients who are most likely to repeat suicidal behaviors presents a serious challenge to clinicians.…”
Section: Introductionmentioning
confidence: 99%